Rehabilitation of Adults with Fibromyalgia - Su Yi Lee; Krystal Song; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2025)
Fibromyalgia syndrome is an increasingly recognized chronic musculoskeletal disorder, involving widespread pain, soft tissue tenderness, other somatic complaints, physical deconditioning, cognitive impairment, psychological issues and disability. It adversely impacts mobility, activities of daily living, work productivity, societal participation and quality of life. Multidisciplinary rehabilitation approaches are often required for prompt recognition of impairments related to fibromyalgia and formulation of an individualized rehabilitation plan to assist patients in relieving symptoms, improve mobility, daily and psychosocial functioning, as well as quality of life. To date, there appears to be little scientific evidence for the effectiveness of rehabilitation interventions for fibromyalgia. However, rehabilitation strategies remain commonly used as an approach for this condition, which causes much personal and substantial economic loss to society. We aim to summarize the current evidence for the effectiveness of rehabilitation interventions used for fibromyalgia among working age adults, including pharmacological and non-pharmacological management approaches. Keywords: Fibromyalgia, rehabilitation, treatment, intervention, evidence-based, medication.